2004
DOI: 10.1158/0008-5472.can-03-3693
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Regulates Migration and Development of Human Acute Myelogenous Leukemia Stem Cells in Transplanted NOD/SCID Mice

Abstract: The chemokine stromal cell-derived factor-1 (SDF-1) and its receptor CXCR4 participate in the retention of normal hematopoietic stem cells within the bone marrow (BM) and their release into the circulation. Homing and engraftment of human stem cells in immunodeficient mice are dependent on cell surface CXCR4 expression and the production of BM SDF-1, which acts also as a survival factor for both human and murine stem cells. However, the role of SDF-1/CXCR4 interactions in the control of human acute myelogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
272
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(281 citation statements)
references
References 59 publications
8
272
1
Order By: Relevance
“…106,108 CXCR4 receptors are functional in AML, 58,109 and surface CXCR4 expression, which is generally low when compared with lymphoid cells, correlates with functional responses, such as chemotaxis. 110 CXCR4-dependent engraftment of AML cells in non-obese diabetic/severe combined immunodeficient (NOD/SCID) mice was demonstrated by Tavor et al, 111 and this group also reported that the proteolytic enzyme elastase is involved in regulating SDF-1-dependent migration and proliferation of AML cells in vitro and in vivo. 112 CXCR4, in cooperation with VLA-4 integrins, mediates spontaneous migration of AML cells beneath MSCs, along with a decreased proliferation of migrated AML cells within stromal layers.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 94%
“…106,108 CXCR4 receptors are functional in AML, 58,109 and surface CXCR4 expression, which is generally low when compared with lymphoid cells, correlates with functional responses, such as chemotaxis. 110 CXCR4-dependent engraftment of AML cells in non-obese diabetic/severe combined immunodeficient (NOD/SCID) mice was demonstrated by Tavor et al, 111 and this group also reported that the proteolytic enzyme elastase is involved in regulating SDF-1-dependent migration and proliferation of AML cells in vitro and in vivo. 112 CXCR4, in cooperation with VLA-4 integrins, mediates spontaneous migration of AML cells beneath MSCs, along with a decreased proliferation of migrated AML cells within stromal layers.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 94%
“…The dose of total body irradiation (TBI) depended on the mouse strains and also on the source and irradiator. It usually varied from 2 Gy to 4Gy (Chelstrom et al, 1994;Tavor et al, 2004;Liu et al, 2007;Sanchez et al, 2009). Mice should be kept in a specific pathogenfree environment with acidified water at least one week before receiving pretreatment.…”
Section: Xenogeneic Transplantation and Assessment Of Engraftmentmentioning
confidence: 99%
“…Additionally, CXCR4 also influenced engraftment of human AML in the immunodeficient mice. CXCR4 played a important role in the control of human AML cell trafficking and disease progression, and CXCR4 antibodies or CXCR4 inhibitors blocked AML cells homing into the BM and spleen of transplanted mice (Tavor et al, 2004;Zhang et al, 2012b). Another study demonstrated that CXCR4 was not critical for the engraftment of AML CD34+ cells in NOD/SCID mice (Monaco et al, 2004).…”
Section: Factors Influencing Engraftment Of Human Aml In Immunodeficimentioning
confidence: 99%
“…CXCR4 and its ligand (chemokine stromal-derived factor 1a) are critical components of the stromal-leukemia cell interface. CXCR4 has an important role in cell adhesion-mediated drug resistance 100,101 and, interestingly, is found more abundantly in FLT3-ITD AML samples than in FLT3-wild-type samples. 102 CXCR4 inhibition results in disruption of AML-niche interactions and sensitizes leukemic blasts to cytotoxic chemotherapy.…”
Section: Flt3 Monoclonal Anitbodiesmentioning
confidence: 99%